Depression and metabolic syndrome across epidemiological transition - Dikoko, Viwe (Department of Public Health and Family Medicine, 2025)
Background: Depression and metabolic syndrome (MetS) are growing global health concerns, but limited research focuses on African-origin populations. This study investigates the association between MetS and depression among individuals in Ghana, South Africa (SA), Jamaica, Seychelles, and the United States (US), emphasizing gender and regional disparities. Methods: Secondary data of 446 participants from the METS (2008-2010) and METS- Microbiome study (2017-2019), a prospective cohort, were analyzed. MetS was defined as meeting at least three of the following criteria: elevated blood pressure, low HDL(High- Density Lipoprotein), elevated triglycerides, or high glucose. Depression was assessed using the CES-D scale (score ≥16 indicating depressive symptoms). Depression was assessed only at follow-up (2019), while MetS was measured at baseline (2010). Logistic regression examined the MetS-depression relationship, stratified by gender, adjusting for demographic and behavioural factors. Findings: The prevalence of MetS was 12% in Ghana (N=23), 17% in SA (N=9), 29% in Jamaica (N=26), 27% in Seychelles (N=33), and 39% in the US (N=36). The prevalence of depression was 15% in Ghana (N=29), 25% in SA (N=13), 18% in Jamaica (N=16), 9% in Seychelles (N=11) and 33% in the US (N=30). No significant overall association between MetS and depression was found. However, in men, individual MetS components showed weak associations at p < 0.1. High blood pressure (OR = 3.46, p<0.1) and low HDL (OR = 3.45, p<0.1) were associated with higher odds of depression, while obesity appeared protective (OR = 0.20, p<0.1). Women showed higher rates of obesity, abdominal adiposity, and depression, particularly in Jamaica, Seychelles, and the US. Age inversely correlated with depression in both genders, with older individuals reporting fewer symptoms. Regionally, living in Ghana, Seychelles, and Jamaica was linked to lower odds of depression compared to the US. Interpretation: This study highlights significant gender and regional differences in the MetS-depression relationship. Women face greater vulnerabilities related to obesity and psychological distress, while men are at higher risk due to elevated blood pressure and low HDL. Tailored public health strategies are needed to address these distinct risks and regional disparities, focusing on mitigating the dual burden of metabolic and mental health challenges. Policy strategies should prioritize integrated screening, targeted education, and community-based services—particularly in low-resource settings—to reduce the dual burden of MetS and depression in populations of African origin.